Evolving symptom networks in relation to HIV-positive duration among people living with HIV: A network analysis. (July 2021) - Zhu, Zheng; Wen, Huan; Yang, Zhongfang; Han, Shuyu; Fu, Yanfen; Zhang, Lin; Hu, Yan; Wu, Bei
Highlights: Assessment of symptom networks needs to be part of people living with HIV (PLWH) care. PLWH who had been diagnosed >10 years prior had less severe symptoms. PLWH who had been diagnosed >10 years prior had a denser symptom network. Fatigue was the most central symptom in PLWH with <10 years HIV duration. Cognitive symptoms were the most central symptoms in >10 years HIV duration group. Abstract: Objectives: To explore and visualize the relationships among multiple symptoms in people living with HIV (PLWH) and compare centrality indices and the density of symptom networks among groups of individuals with different HIV-positive durations. Methods: We conducted a secondary analysis of data from the HIV-related Symptoms Monitoring Survey conducted in China. Networks were constructed among 27 symptoms. Centrality properties, including strength and closeness, and network density were used to describe relationships among symptoms in 5 different HIV-positive duration groups. Results: The findings showed that PLWH with longer HIV-positive durations did not have more severe symptoms; instead, their symptom networks were denser than those of their newly HIV-diagnosed counterparts ( F = 27.073, P < 0.001). Fatigue was the most severe and central symptom in PLWH with an HIV-positive duration <10 years (rS = 7.79–10.09, rB = 18–44, rC = 0.01). Confusion was the most central symptom across the 3 centrality indices (rS = 11.81, rB = 14.00, rC = 0.02) in PLWH who had HIV-positive durations >10 years. Conclusion: This study demonstrates a need to include an assessment of PLWH symptom networks as an essential component of HIV care. We recommended evaluating cognitive function and cognitive training as essential components of HIV care for long-term survivors, even in younger populations (aged ≤50 years).